Penerapan Penentuan Harga Jual Metode Cost Plus Pricing Pada UKM di Surabaya - Nanang Shonhadji; Ririn Poerwanti; Ali Soebijanto (-, 2022)
Financial reports function as a tool to analyze financial performance that can provide information for decision making. The object of this service is aimed at small and medium enterprises (SMEs) engaged in the manufacturing business in Surabaya. The purpose of this service program is to implement a model and design for calculating selling prices using the cost plus pricing method as part of preparing structured financial reports that are easy for SMEs to understand. The method of implementing community service is carried out by providing training, mentoring and mentoring for SMEs to prepare the cost of goods sold. The obstacle faced by partners is that there are problems in determining selling prices, namely (a) SMEs have not been able to identify costs based on cost sources, but SMEs only distinguish costs into two groups, namely operational costs and non-operational costs, the impact of which is calculated as the cost of production to become not accurate. (b) The SME party must make a markup based on the expected profit target estimate so that the selling price offered is the selling price that is marked up to the desired conditions. (c) SMEs have not been able to identify the costs that trigger the occurrence of inherent costs forming the cost of goods sold. The results of community service provide awareness and knowledge for SMEs to compile the cost of production and determine the selling price using the full costing method.